Exploring the deployment and reintegration experiences of active duty military families with young children. Issue 8 (17th November 2017) - Strong, Jessica; Lee, Jacquelyn J.
ABSTRACT: Active duty military families are experiencing increased stress as service members deploy to and return from lengthy and repeated deployments to multiple war zones. These deployments have a cumulative impact on the behavioral health and well-being of not only the service member, but also the family, particularly in families with very young children (Lester et al., 2016). Emergent research concerning families with young suggests that greater attention to the military spouse is needed to ensure effective, supportive service provision for these families. The purpose of the present study is threefold: (1) to identify the challenges faced by families with young children during and after deployment, (2) to understand resource utilization by these families, and (3) to explore the strengths and strategies used during these experiences. Data were collected through semi-structured interviews with 19 active duty Marine Corps family members with young children (under 5 years old) and 10 key program providers on or near a large military base in the southeast region of the United States. Findings reveal significant social isolation, which is consistent with the literature, the need for formal and informal social supports as well as self-care for the at-home parent, challenges in co-parenting and utilizing known resources, and a range of strategies used to manage deployment and reintegration. Implications for practice are discussed.